Developing Model of Basic Science Learning Management on Universal World’s to Knowledge Quest Integrated for Enhancing Achievement of 12 Great Students - Chatthai, Saichon; Jedaman, Pornchai; Kantamas, Kannikar; Meunchong, Wanwisa (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
Learning management design, appropriate and environment conducive in the learning of students were stimulating responses to learners and have to diversity and is ready for learners to learn while they are interested in learning to efficiency. Specific purposes of developing a model of basic science learning management on universal Worlds to knowledge quest integrated for enhancing the achievement of 12 great students. The collection came from the documentary study, the practice meeting, assessment of the model by the evaluate questionnaire, learning management, the assessment and questionnaire, the test of achievement to the data. The findings show that the guidelines levels, the factors and indicators on the model, suitability levels to model, the efficiency of learning management, students’ achievement, include the satisfaction levels to model.